Can a single pulse transcranial magnetic stimulation targeted to the motor cortex interrupt pain processing? - Kisler, Lee-Bareket (PLoS One, 2018)
The modulatory role of the primary motor cortex (M1), reflected by an inhibitory effect of M1-stimulation on clinical pain, motivated us to deepen our understanding of M1’s role in pain modulation. We used Transcranial Magnetic Stimulation (TMS)-induced virtual lesion (VL) to interrupt with M1 activity during noxious heat pain. We hypothesized that TMS-VL will effect experimental pain ratings. Three VL protocols were applied consisting of single-pulse TMS to transiently interfere with right M1 activity: (1) VL(M1)- TMS applied to 11 subjects, 20 msec before the individual’s first pain-related M1 peak activation, as determined by source analysis (sLORETA), (2) VL(-50) (N = 16; TMS applied 50 ms prior to noxious stimulus onset), and (3) VL(+150) (N = 16; TMS applied 150 ms after noxious stimulus onset). Each protocol included 3 conditions ('pain-alone', ' TMS-VL', and ‘SHAM-VL’), each consisted of 30 noxious heat stimuli. Pain ratings were compared, in each protocol, for TMS-VL vs. SHAM-VL and vs. pain-alone conditions. Repeated measures analysis of variance, corrected for multiple comparisons revealed no significant differences in the pain ratings between the different conditions within each protocol. Therefore, our results from this exploratory study suggest that a single pulse TMS-induced VL that is targeted to M1 failed to interrupt experimental pain processing in the specific three stimulation timing examined here.